Description of a new species of Kermicus Newstead (Hemiptera: Coccomorpha: Pseudococcidae) from bamboo in southeast China - Wu, San-An; Huang, Shaobin; Liang, Chuanguan (Zootaxa, 2020)
A new species, Kermicus huizhouensis Wu & Huang sp. n. (Hemiptera: Coccomorpha: Pseudococcidae), is described and illustrated based on the adult female, second instar female and first-instar nymph. It was collected at Qianfeng village, Huiyang District, Huizhou City, Guangdong Province, P. R. China, inside the stem of bamboo Bambusa rigida (Poaceae) and attended by the ant Tetraponera binghami (Forel) (Hymenoptera: Formicidae). It differs from K. wroughtoni Newstead, 1897 by the adult female lacking multilocular disc pores in the marginal region of the venter, and both the adult female and first-instar nymph having the anal ring bearing 16–20 setae. Keys to genera of legless mealybugs on bamboo based on adult females, and the immature stages of Kermicus, are provided.